Performance and Economic Analysis of Concentrated Solar Power Generation for Pakistan - Soomro, Mujeeb Iqbal; Mengal, Abdullah; Memon, Yasir Aftab; M., Waris; Shafiq, Qadir Nawaz; Mirjat, Nayyar Hussain (MDPI AG, 2019)
In Pakistan, the utilization of renewable energy sources is increasing in order to reduce the electricity supply and demand gap. However, concentrated solar power (CSP) generation has not been considered in the country even though it has gained considerable attention worldwide. This study, as such, investigates the potential, performance, and economic analyses of four CSP technologies for different locations in Pakistan. Initially, an assessment of CSP sites, including solar resource, land, and water availability, was undertaken. Then, performance simulations of CSP technologies for four different locations of Pakistan, namely Quetta, Hyderabad, Multan, and Peshawar, were examined. For all cases, highest energy production was achieved in summers and lowest in winters, and CSP plants with evaporative cooling were found to be efficient compared to air cooling. The results also revealed that the Quetta and Hyderabad regions were promising for CSP development while parabolic tough (PT) and solar power tower (SPT) were the suitable CSP technologies for these regions. Specifically, the SPT plant with air cooling could be a favorable option for energy production in Quetta. Lastly, economic analyses revealed the financial feasibility of CSP plants in Pakistan since the levelized cost of energy is found to be significantly low.